(untitled) (Journal of Medicine, 2014)
Visceral Leishmaniasis is a very common but neglected disorder in Bangladesh. It can remain subclinical or become symptomatic with an acute, sub acute or chronic course. Atypical presentations can be equally challenging to the clinician. Visceral leishmaniasis is associated with various autoimmune phenomena. Sometimes it can mimic any autoimmune disorders including Autoimmune Hemolytic Anemia (AIHA), SLE, and Rheumatoid Arthritis etc. Here, we describe a case of visceral leishmaniasis with Coombs positive autoimmune hemolytic anemia. DOI: http://dx.doi.org/10.3329/jom.v14i2.19686 J Medicine 2013, 14(2): 198-200